Safety and efficacy assessment of two new leprosy skin test antigens: randomized double blind clinical study. - Becky L Rivoire; Nathan A Groathouse; Stephen TerLouw; Kapil Dev Neupane; Chaman Ranjit; Bishwa Raj Sapkota; Saraswoti Khadge; Chhatra B Kunwar; Murdo Macdonald; Rachel Hawksworth; Min B Thapa; Deanna A Hagge; et al. (Public Library of Science (PLoS), 2014)
New tools are required for the diagnosis of pre-symptomatic leprosy towards further reduction of disease burden and its associated reactions. To address this need, two new skin test antigens were developed to assess safety and efficacy in human trials.A Phase I safety trial was first conducted in a non-endemic region for leprosy (U.S.A.). Healthy non-exposed subjects (n = 10) received three titrated doses (2.5 µg, 1.0 µg and 0.1 µg) of MLSA-LAM (n = 5) or MLCwA (n = 5) and control antigens [Rees MLSA (1.0 µg) and saline]. A randomized double blind Phase II safety and efficacy trial followed in an endemic region for leprosy (Nepal), but involved only the 1.0 µg (high dose) and 0.1 µg (low dose) of each antigen; Tuberculin PPD served as a control antigen. This Phase II safety and efficacy trial consisted of three Stages: Stage A and B studies were an expansion of Phase I involving 10 and 90 subjects respectively, and Stage C was then conducted in two parts (high dose and low dose), each enrolling 80 participants: 20 borderline lepromatous/lepromatous (BL/LL) leprosy patients, 20 borderline tuberculoid/tuberculoid (BT/TT) leprosy patients, 20 household contacts of leprosy patients (HC), and 20 tuberculosis (TB) patients. The primary outcome measure for the skin test was delayed type hypersensitivity induration.In the small Phase I safety trial, reactions were primarily against the 2.5 µg dose of both antigens and Rees control antigen, which were then excluded from subsequent studies. In the Phase II, Stage A/B ramped-up safety study, 26% of subjects (13 of 50) showed induration against the high dose of each antigen, and 4% (2 of 50) reacted to the low dose of MLSA-LAM. Phase II, Stage C safety and initial efficacy trial showed that both antigens at the low dose exhibited low sensitivity at 20% and 25% in BT/TT leprosy patients, but high specificity at 100% and 95% compared to TB patients. The high dose of both antigens showed lower specificity (70% and 60%) and sensitivity (10% and 15%). BL/LL leprosy patients were anergic to the leprosy antigens.MLSA-LAM and MLCwA at both high (1.0 µg) and low (0.1 µg) doses were found to be safe for use in humans without known exposure to leprosy and in target populations. At a sensitivity rate of 20-25% these antigens are not suitable as a skin test for the detection of the early stages of leprosy infection; however, the degree of specificity is impressive given the presence of cross-reactive antigens in these complex native M. leprae preparations.ClinicalTrials.gov NCT01920750 (Phase I), NCT00128193 (Phase II).